O professor de PLE em formação - Severino, Cintia do Nascimento [UNESP]; Rocha, Nildicéia Aparecida [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The work intends to focus on the experiments experienced by a graduate student in his initial training in the course of letters, which during its participation in the extension project "teaching Portuguese as a foreign language (PLE) for foreigners", which has performed a reflection theoretical methodological about their training and expertise as a teacher of Portuguese language.

O trabalho pretende focalizar as experiências vivenciadas por uma aluna da graduação em sua formação inicial no Curso de Letras, que durante sua participação no Projeto de Extensão "Ensino de Português como Língua Estrangeira (PLE) para estrangeiros", que tem realizado uma reflexão teórico-metodológica sobre sua formação e atuação como professora de português língua estrangeira.
Keywords: Teacher training; Teacher; Portuguese foreign language; Formação; Professor; PLE